Design of cosmic veto shielding for HPGe-detector spectrometer. (March 2016) - Hu, Qingdong; Ma, Hao; He, Jianhua; Zeng, Zhi; Zeng, Ming; Li, Tenglin; Li, Yiliang; Yi, Hongchang; Cheng, Jianping; Li, Junli
Abstract: A Monte Carlo simulation to optimize the shielding design of a cosmic-veto HPGe spectrometer is described. The incident sources were simulated using the CRY code and the effect on the integral background count rate of different shielding structures was evaluated using the simulation code GEANT4 with application of veto mechanics during simulation. This procedure has been validated by experimental results, and another optimized cosmic veto shielding for an HPGe-detector has been illustrated. Highlights: A Monte Carlo simulation of the cosmic veto shielding for a gamma-ray spectrometer. The simulation is validated using experimental results. An optimized cosmic veto shielding with our procedure is illustrated.